Pengaruh Penerapan Coaching, Mentoring, dan Counseling (CMC) Terhadap Kinerja Karyawan pada Bidang P2TL PT PLN Electric Services - Dani Fachrudin; Sari Laelatul Qodriah; Ali Jufri (INDO PUBLISHING, 2026)
This study aims to analyze the effect of implementing Coaching, Mentoring, and Counseling (CMC) on employee performance in the P2TL division of PT PLN Electric Services UL Karawang. The research employs a quantitative explanatory approach using total sampling of all employees in the division. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) through SmartPLS to assess validity, reliability, and the relationships among variables. The findings indicate that Coaching, Mentoring, and Counseling each have a positive and significant effect on employee performance. Among the three variables, Mentoring provides the most dominant contribution to performance improvement. Simultaneously, the implementation of these three approaches significantly influences employee performance and explains a substantial portion of performance variation within the research model. These findings confirm that the integrated application of CMC enhances technical competence, work motivation, and psychological well-being, which ultimately leads to sustainable performance improvement in a work environment that requires accuracy and professionalism.